STRATEGI PENGELOLAAN KEUANGAN SEKOLAH MELALUI PENDEKATAN GREEN ACCOUNTING DI SMK INFORMATIKA SERANG - Mega Arum; Putri Wulandari (LPPM Universitas Bina Bangsa, 2024)
This study aims to explore and analyze the implementation of Green Accounting as a financial management strategy in schools. Green Accounting, or environmental accounting, is an approach that integrates environmental aspects into the financial management process, with the primary goal of improving resource efficiency and minimizing negative environmental impacts. Through a case study in several schools in Indonesia, this research identifies various Green Accounting practices that have been implemented and measures their positive impact on school financial management. The results of the study indicate that the implementation of Green Accounting can increase environmental awareness among students and school staff, and significantly contribute to reducing operational costs through more efficient resource management. Additionally, schools adopting this approach also demonstrate improvements in waste management and energy usage. These findings indicate that Green Accounting is not only beneficial for the environment but also provides economic benefits for educational institutions. Therefore, this research suggests that schools integrate Green Accounting into financial management policies and practices as a strategic step towards sustainability. The implementation of this approach is expected to cultivate a younger generation that is more environmentally conscious and capable of managing resources wisely in the future